Helical Force Impact on Nonlinear Rotating Convection of a Couple-Stress Fluid - Nagaraju, J.; Babu, K. Ramesh; Reddy, M. Pavan Kumar (Journal of Applied Nonlinear Dynamics, 2026)
The current investigation addresses the impact of helical force and coriolis effect on linear and nonlinear stability analyses of a couple stress fluid. Normal mode approach is employed to solve the non-dimensional governing equations. The corresponding eigenvalue problem is solved analytically using one-term Galerkin method. The influence of different physical parameters on the system are presented graphically. Ginzburg - Landau equation is derived to analyze the convection heat transport. Helical force parameter has the destabilizing nature on the system. For oscillatory instability, Prandtl number has a destabilizing factor for the system to become unstable. For oscillatory as well as steady instability, the critical thermal Rayleigh number is observed to increase with enhancement in Couple stress parameter and Taylor number.